Acercamiento a la situacion socioeconomica de las comunidades campesinas del Departamento de Sucre desde la perspectiva del Programa Yuquero - Souza, C.M. de; Ríos V., W.; Lima, J.A. de M.; Álvarez B., M.E.; Portillo M., R.; León B., A.; Muñoz H., R.; Rojo, J.A. (International Center for Tropical Agriculture, 1987)
An overview is given of the situation of farm communities in the dept. of Sucre, Colombia, where a cassava drying program operates. The lack of integration of the developmental activities carried out by different institutions is evident, indicating the need for greater participation in district planning. Since a trend to monocrop cassava was observed, more attention should be paid to agricultural diversification. An animal feed industry using dried cassava should be installed. Several technical aspects of agricultural production are also discussed such as mechanization, intercropping, plant density, improved technology, and income. Recommendations are also given regarding the current underutilization of the machinery of the existing agroindustries, the improvement of sanitary conditions in the plants, and the enforcement of basic industrial security measures. Product quality control should be conducted, especially regarding MC. Conditions favoring a greater participation of members in farmer organizations should be sought, in addition to enhanced institutional support in the search for a more integrated approach to regional development. (CIAT)